DEPRIVATION OF LIBERTY IN CROATIAN MISDEMEANOUR PROCEEDINGS - APPLICATION OF EUROPEAN DETENTION AND PENITENTIARY STANDARDS (EU and comparative law issues and challenges series (ECLIC), 2024)
The paper addresses the issue of deprivation of liberty in misdemeanour proceedings in the context of both pre-trial detention standards and penitentiary standards set out in the practice of the European Court of Human Rights and the documents of the European Union. The fundamental human right to liberty can be restricted in misdemeanour proceedings in accordance with the Misdemeanour Act of the Republic of Croatia, following a police arrest or based on a court decision on detention to ensure the defendant's presence. The paper aims to analyse material and procedural conditions for the arrest and detention, and the conditions for the execution of both the detention measure and the prison sentence imposed in misdemeanour proceedings within the Croatian prison system.In addition to the rich jurisprudence of the European Court of Human Rights, which has been developing and strengthening detention standards and the rights of prisoners for decades, the past decade has been marked by intensive activities of the European Union in matters related to persons deprived of their liberty in criminal proceedings. Considering that the issue of deprivation of liberty in misdemeanour proceedings has not been systematically addressed in Croatian literature, the paper will particularly analyse how these standards established in binding and non-binding legal instruments apply to and affect issues related to deprivation of liberty in Croatian misdemeanour proceedings.